The study of urban waste management through the role of youth as an effort to protect Sinjai area, South Sulawesi Province, Indonesia. Issue 1 (April 2020) - Waris, A; Rashid, A; Rahim, I R
Abstract: This study aims to determine the potential and new models and motivation of youth in urban waste management. This research method conducted using descriptive data collection using a questionnaire in the form of Google Form and interviews with the Department of Environment and Forestry and the determination of waste management models using SWOT analysis (Strength, Weakness, Opportunity, and Threats). The number of the questioner is 150 with the characteristics of respondents aged 16-30 years. The results showed that the attitude of the youth in waste management in Sinjai has the lowest rank, especially in waste management and utilization of waste generated. It is shown by the scale of 100% is obtained 63% of youth do not perform sorting of waste and 64% of youth do not perform using waste.